Association of Red Meat and Poultry Consumption With the Risk of Metabolic Syndrome: A Meta-Analysis of Prospective Cohort Studies - Guo, Hongbin; Ding, Jun; Liang, Jieyu; Zhang, Yi (Frontiers in Nutrition, 2021)
Objectives: To examine the associations of red meat and poultry consumption with the risk of metabolic syndrome (MetS). Methods: A comprehensive literature search in the databases of PubMed, Web of Science and Embase (up to March 2021), was conducted to identify the prospective cohort studies concerning the associations of red meat and poultry consumption with the risk of MetS. The pooled relative risk (RR) of MetS for the highest versus lowest category of red meat and poultry consumption, as well as their corresponding 95% confidence interval (CI) were calculated. Results: A total of 9 prospective cohort studies, which involved a total of 21869 participants, were included in this meta-analysis. Specifically, 8 studies were related to red meat consumption, and the overall multi-variable adjusted RR showed that red meat consumption was associated with a higher risk of MetS (RR=1.35, 95% CI: 1.13 to 1.62; P=0.001). Moreover, 4 and 3 studies were related to processed red meat and unprocessed red meat consumption, respectively. Both processed (RR=1.48, 95% CI: 1.11 to 1.97; P=0.007) and unprocessed red meat (RR=1.32, 95% CI: 1.14 to 1.54; P=0.0003) was associated with a higher risk of MetS. In the 3 studies related to poultry consumption, the overall multi-variable adjusted RR suggested that poultry consumption was associated with a lower risk of MetS (RR=0.85, 95% CI: 0.75 to 0.97; P=0.02). Conclusions: The current evidence suggests that red meat (both processed and unprocessed) consumption is associated with a higher risk of MetS, whereas poultry consumption is associated with a lower risk of MetS. More well-designed prospective cohort studies and randomized controlled trials are needed to elaborate the concerned issues further.